Effects of Brainstorming and Field Trips Teaching Methods n Junior Secondary School Students’ Learning Outcomes in Business Studies in Rivers State, Nigeria (2016)
In Nigeria, Business studies is one of the subjects offered in Junior Secondary Schools (JSS) as a practical subject meant to expose learners to commerce, office management, trade and book keeping. In spite of its importance, performance in the subject is below expectation in Nigeria and Rivers State in particular. Previous studies revealed that teaching methods such as brainstorming and field trip will improve learning outcomes but they are rarely used while teaching Business Studies. This study, therefore, determined the effects of brainstorming teaching method (BTM), field trip teaching method (FTTM), and conventional teaching method (CM) on secondary school students‟ learning outcomes in Business Studies. It also examined the moderating effects of gender and personality trait. Bandura‟s social learning and Vygotsky constructivism theories of learning provided the framework for the study while the pretest-posttest, control group in a quasi – experimental design with 3x2x2 factorial matrix was adopted. Purposive sampling technique was used to select six public junior secondary schools in Emohua Local Government Area (LGA). The data from Rivers State Ministry of Education revealed that students from the LGA had the least performance in Business Studies. All the JSS 2 students (467) in the selected schools participated during the pretest when personality trait scale was administered. Students that scored below 59 were regarded as introverts while those who scored 60 and above were the extroverts. The test result was used to select 144 students (72 intoverts-36 males and 36 females as well as 72 extroverts-36 males and 36 females) who were grouped equally into experimental and control groups. The treatment lasted for seven weeks. The instruments used were: Business Studies Achievement Test (r=0.82), Attitude to Business Studies (α=0.72) and Personality trait (α= 0.75) questionnaires. Data collected was analysed using Analysis of Covariance (ANCOVA) at 0.05 level of significance. There was a significant main effect of treatments on students‟ achievement in Business Studies [F(2,131)=26.70, partial η2=0.29]. Participants in FTTM had the highest mean (35.79), followed by BTM (35.71) and CM (27.54). There was significant effect of treatments on students‟ attitude to Business studies, [F(2,131)=27.70, partial η2=0.29] with FTTM ( x =94.94), BTM ( x =88.00), and CM ( x =84.90). There were significant interaction effects of treatment and personality trait on students‟ achievement [F(2,131)=4.40, η2 = 0.63]. Introverts in BTM had a higher mean score of (37.69) than extroverts (33.72) while introverts in FTTM scored (35.97) is slightly higher than extroverts (35.50). Extrovert in CM had higher mean score (29.21) than introvert (25.23). There was significant interaction effect of gender and personality trait on students attitude in Business Studies (F(1,131)= 4.90, η2 = 0.36]. Male introverts had a higher mean scores (90.13) than female introverts (86.52), while female extroverts had a higher mean score (96.40) than male extroverts (86.06). There was no 3-way interaction effect. Brainstorming and Field trip teaching methods influenced learning outcomes of students in Business studies in Rivers state but Field trip method was better. Teachers should be encouraged to use both methods during Business studies classes